Water contingency: water woe's end needs a rethink - Zainuddin, Zaki (New Straits Times Press (NSTP), 2014)
THE water rationing exercise in the Klang Valley was recently extended to the end of the month. Apparently, the earlier exercise only yielded seven per cent savings. This was not surprising as the ration was not specifically done "over volume" but "over time" ( two days on, two days off).